Estimation of Heterosis Among Potato (Solanum tuberosum L.) Crosses in Ethiopia - Workayehu, Manamno; Mohammed, Wassu; Abebe, Tesfaye (Journal of Tropical Crop Science, 2021)
Determination of heterosis in tetraploid potato crosses is necessary for identification of superior genotypes for variety development or breeding program. However, producing heterotic potato genotypes through local crossing is not a common practice in Ethiopia. Hence, this study was conducted to estimate the magnitude of better, and standard check heteroses in potato clones that are produced from local crossing. This will help identify potential of hybrid for future breeding schemes. Heterosis of 75 clones were evaluated using a 9 x 9 Simple Lattice design. Results of the analysis of variance showed significant differences for all the growth characters, except medium-sized tubers and specific gravity of tuber. These results indicate the presence of genetic variability among the samples. The clones exhibited as high as 55.62 and 58.31 t.ha-1 marketable and total tuber yield, respectively. These clones also displayed mid, better parent and standard heterosis of 118.8%, 90.5% and 239.1%, respectively, for marketable tuber yield. This result indicates the presence of high magnitude heterosis which could be used to exploit the hybrid vigor. In addition, mid, better parent, and standard check heterosis were estimated at 79.36%, 61.04% and 209.17% for total tuber yield, respectively. Our results show the highest chance of getting heterotic offspring than parental and standard check varieties to developing new potato varieties. The information generated from this study would be valuable for researchers who intend to develop high-yielding varieties of potato